Academic Honesty in University Students: A Systematic Review of Trends, Challenges, and Interventions - Awalya Siska Pratiwi; Arbin Janu Setiyowati; Adi Atmoko; Diniy Hidayatur Rahman (The Indonesian Institute of Science and Technology Research, 2026)
The literature also points to communication as a critical dimension of academic honesty. In light of these complexities, this systematic literature review (SLR) seeks to synthesize research published between 2015 and 2025 on academic honesty among university students. The remainder of this paper is structured as follows. First, the methodological framework for the review is described, including inclusion and exclusion criteria aligned with PRISMA guidelines. Second, the results section presents a thematic synthesis of the literature. This study employed a Systematic Literature Review (SLR) approach, guided by the PRISMA 2020 protocol, to ensure transparency, replicability, and alignment with standards used in Scopus-indexed publications. The findings underscore that punitive approaches alone are insufficient. Instead, universities must adopt integrated strategies that combine pedagogical innovations, transparent communication, emotional intelligence training, and AI literacy programs. Evidence from diverse contexts indicates that participatory and preventive measures, such as game-based learning and contextual discovery approaches, can effectively foster student ownership of integrity. At the same time, localized adaptations are essential, as cultural and contextual variations strongly influence perceptions and practices of honesty. Theoretically, this review contributes by positioning academic honesty not merely as rule compliance, but as an integral component of professional identity formation and ethical development in higher education. Practically, the findings inform institutional policy by highlighting the need for integrated integrity frameworks that balance regulation, education, and student participation. For teaching practice, the review underscores the effectiveness of contextual learning models, game-based interventions, and explicit integrity instruction embedded within curricula.